The A3 adenosine receptor as multifaceted therapeutic target: pharmacology, medicinal chemistry, and in silico approaches. Issue 2 (16th November 2011) - Cheong, Siew Lee; Federico, Stephanie; Venkatesan, Gopalakrishnan; Mandel, Alexander Laurence; Shao, Yi‐Ming; Moro, Stefano; Spalluto, Giampiero; Pastorin, Giorgia
Abstract Adenosine is an ubiquitous local modulator that regulates various physiological and pathological functions by stimulating four membrane receptors, namely A1, A2A, A2B, and A3. Among these G protein‐coupled receptors, the A3 subtype is found mainly in the lung, liver, heart, eyes, and brain in our body. It has been associated with cerebroprotection and cardioprotection, as well as modulation of cellular growth upon its selective activation. On the other hand, its inhibition by selective antagonists has been reported to be potentially useful in the treatment of pathological conditions including glaucoma, inflammatory diseases, and cancer. In this review, we focused on the pharmacology and the therapeutic implications of the human (h)A3 adenosine receptor (AR), together with an overview on the progress of hA3AR agonists, antagonists, allosteric modulators, and radioligands, as well as on the recent advances pertaining to the computational approaches (e.g., quantitative structure–activity relationships, homology modeling, molecular docking, and molecular dynamics simulations) applied to the modeling of hA3AR and drug design. © 2011 Wiley Periodicals, Inc. Med Res Rev